Some Remarks on the Problem of Dollar Scarcity - Tinbergen, J. (Econometrica, 1949)
At the prevailing exchange rates and price levels it appears that, considering the current items of the balance of payments of the United States, demand for dollars surpasses their supply. Or in other terms: American exports to the rest of the world (taking goods and services together) surpass imports from the other countries. For the moment, one of the chief reasons is the heavy reconstruction demand in many countries, particularly European, together with the low level of productivity in these areas. Many experts expect, however, that the disequilibrium will remain to some extent after the reconstruction period. The possibility of a permanent disequilibrium will hamper, they fear, even the action needed to solve the temporary dificulties. Granting credits for reconstruction to war-hit countries is not attractive unless in the long run an equilibrium will develop. It seems worth while, therefore, to investigate in some more detail the possibilities of restoring the equilibrium in the current items of the American balance of payments.